DEVELOPMENT OF SPIN WHEEL TO TEACH EXPLANATORY TEXT IN WRITING SKILL FOR ELEVENTH GRADE - Adinda Rastavala; Ahmad Saifudin; Istina Atul Makrifah (PROJECT (Professional Journal of English Education), 2023)
The aims of this research is to find out the processes and results in developing spin wheels for teaching explanatory text especially in writing skill. This research was conducted because students had difficulty in producing a text. Besides that, the lack of supporting media is also a factor students getting bored in learning. The technique used by the researcher was direct observation and unstructured interview with the English teacher and all student class XI MIA of MA Bustanul Mutaallimin. Researcher also distributed questionnaires to all students at the end of the study to find out whether the spin wheel was decent or not. The media that developed by researcher got a score of 90% from the media expert validation and 87,5% from the material expert validation, both can be said to be “very valid”. While the questionnaire from students responses the researcher got a score 85,75% which means “very decent”. So that, the spin wheel media can be used by the teacher in teaching explanatory text in writing skills to the students.